Towards a Business Process Modeling Technique for Agile Development of Case Management Systems - Ilia Bider; Erik Perjons (Complex Systems Informatics and Modeling Quarterly)
A modern organization needs to adapt its behavior to changes in the business environment by changing its Business Processes (BP) and corresponding Business Process Support (BPS) systems. One way of achieving such adaptability is via separation of the system code from the process description/model by applying the concept of executable process models. Furthermore, to ease introduction of changes, such process model should separate different perspectives, for example, control-flow, human resources, and data perspectives, from each other. In addition, for developing a completely new process, it should be possible to start with a reduced process model to get a BPS system quickly running, and then continue to develop it in an agile manner. This article consists of two parts, the first sets requirements on modeling techniques that could be used in the tools that supports agile development of BPs and BPS systems. The second part suggests a business process modeling technique that allows to start modeling with the data/information perspective which would be appropriate for processes supported by Case or Adaptive Case Management (CM/ACM) systems. In a model produced by this technique, called data-centric business process model, a process instance/case is defined as sequence of states in a specially designed instance database, while the process model is defined as a set of rules that set restrictions on allowed states and transitions between them. The article details the background for the project of developing the data-centric process modeling technique, presents the outline of the structure of the model, and gives formal definitions for a substantial part of the model.